Product design : Mirror frame from Buluh Semantan (gigantochloa scorchtechinii) / Muhamad Hisyam Ahmad - Ahmad, Muhamad Hisyam (Faculty of Applied Sciences, 2016)
The research was handled to investigate the suitability of bamboo as a material for mirror frame using a simple design. Type of bamboo used was buluh semantan (Gigantochaloa scortechinil).The bamboo mirror frame was produced, and the data were collected via survey form. The data analyzed using SPSS based on questionnaire that have been distributed to 101 correspondents. 90% of the total correspondents give positive feedback to the material suitability, product handling and portable, product design, compact design concept, commercialize, product suitability as decoration, product appearance, product color and product price. The idea of producing a bamboo mirror frame will satisfy customer demands and acceptable in the market demands.